Influence of Donor Thickness on Visual Acuity in Descemet’s Stripping Automated Endothelial Keratoplasty - Tomislav Kuzman; Ana Meter; Miro Kalauz; Sanja Masnec; Ivan Škegro; Ivana Jonjić (Journal of Ophthalmic & Vision Research)
Abstract Purpose: Conventional Descemet's Stripping Automated Endothelial Keratoplasty (DSAEK) is a corneal transplantation procedure where the patient's inner dysfunctional layer is replaced with donor lamella. The data currently present in the literature about the correlation between lamellar thickness and visual acuity is sometimes contradictory and lacks clarity. Methods: Study included 55 eyes that underwent the conventional DSAEK procedure. Patients had no other comorbidities that could affect visual acuity. Data about lamellar thickness and visual acuity were measured six months after surgery with anterior segment optical coherent tomography (A5-OCT). Results: The results show that visual acuity before surgery improved from 0.82 to 0.25 logMAR after surgery. Better visual acuity of 0.20 logMAR was achieved with postoperative lamellas thinner than 124 μm, while statistically significantly lower visual acuity of 0.29 logMAR was gained with postoperative lamellas thicker than 124 μm. Conclusion: Our results suggest that the goal after conventional DSAEK is to have postoperative lamellas thinner than 124 μm in the eye, as this will result in better postoperative visual acuity. This value represents the optimal thickness for conventional DSAEK surgery that could minimize tissue loss for eye banks and surgeons may experience fewer problems during surgery, while obtaining good final visual acuity.